Hope Gap [videorecording (DVD)] - Nicholson, William; Bening, Annette; Nighy, Bill, 1949-; O'Connor, Josh; Hart, Aiysha (Screen Media Films, 2020)
Grace lives an idyllic life until her 29-year marriage to Edward abruptly ends, leaving their only son to pick up the pieces. As life unravels, Grace discovers it's never too late to be happy.